NILAI FILOSOFI ORNAMEN LEBAH BERGANTUNG SEBAGAI ASPIRASI PENCIPTAAN LUKISAN KALIGRAFI ISLAM - Armen Titof (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The philosophy of Lebah Begantung ornaments is a sacrifice of self-sacrifice and selflessness, one of the teachings set by the Kampar district society, especially the Pulau Belimbing, which is recommended in daily life for mutual help. So Kampar people learn from nature one of them bee honey. This became the idea of the artist in creating painting which depart from the philosophy of bee ornament depends on the aspiration of the worker. So that cultural heritage can be developed continuously amidst the life of Kampar Malay community, especially Pulau Belimbing hamlet